Mapping the spread of dengue hemorrhagic fever (DHF) with the level of insecurity in Kepahiang Regency in 2021 - Dwitasari, Indah; Trihandini, Indang; Indriyani; Makful, Martya Rahmaniati (Universitas Gadjah Mada, 2023)
Purpose: This study aims to map the distribution of dengue cases in Kepahiang Regency based on the distribution of dengue cases, population density, and air temperature. Furthermore, mapping was carried out based on the level of vulnerability and priority of sub-district-based dengue disease management in Kepahiang Regency. Method: Research using a descriptive method using Geographic Information System (GIS) with scoring and overlay techniques. The data was taken from secondary data from the Kepahiang Regency Health Office and Kepahiang Regency Meteorology and Geophysics Agency in 2021. Results: This study shows that out of 8 sub-districts, there is one with a high level of vulnerability with priority handling, namely Kepahiang Regency. The priority of dengue insecurity can be an effort to prevent and handle dengue disease by the Government. Conclusion: Mapping the level of dengue insecurity in Kepahiang Regency using parameters (dengue cases, population density, and temperature) resulted in 1 in 8 sub-districts being in priority 1 with a high level of insecurity, priority 2 (1 sub-district) with a moderate level of insecurity, priority 3 (1 sub-district) with a low level of insecurity, and priority 4 (5 sub-districts) with a very low level of insecurity.